Effect of Parametric Variations on Electromigration in Integrated Circuits (Global Journal of Science Frontier Research, 2018)
This research paper focuses on the effects of electromigration in integrated circuits at the nanoscale domain. This is an investigative work that shows how various process and parametric variation effects on electromigration. With integrated circuits reaching in the nanoscale domain, electromigration is becoming more of a prominent problem. Being able to find changes into the integrated circuits to provide a better electromigration performance is crucial for future emerging nanotechnologies. Therefore, this paper will go through previous research work to show the evolution of Black's equation and see if Black's equation could use on nanoscale integrated circuits. Also, it will be showing future iterations of the equation and comparing them with constant variables. Besides, a comparison of aluminum and copper interconnects and how electromigration happens differently are also discussing in this paper. Then a conclusion on how Black's equation could use with nanoscale technologies to predict the time during the occurrence of electromigration.
Keywords: activation energy; current density; electromigration; interconnects; integrated circuits; mean time failure